Efektivitas Konseling Gestalt untuk Mengurangi Konsep Diri Negatif Siswa - Gulo, Mei Novita Sarwidar; Lase, Justin Foera-era; Damanik, Hosianna Rodearni; Lase, Famahato (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to examine the effectiveness of Gestalt counseling in reducing negative self-concept among eighth-grade students at SMP Negeri 5 Mandrehe, characterized by feelings of being disliked, irritability, low learning motivation, and poor social adjustment. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design involving 17 students selected through cluster random sampling. Data were collected using a Likert-scale questionnaire that met validity and reliability criteria (Cronbach’s Alpha for the independent variable = 0.917 and dependent variable = 0.896). Data analysis was conducted using a paired sample t-test and N-Gain analysis. The findings revealed a statistically significant difference between pretest and posttest scores (Sig. 0.000 < 0.05; t = 16.577), with a mean N-Gain score of 0.83 (83.30%), categorized as effective. These results indicate that Gestalt counseling is empirically effective in reducing students’ negative self-concept and may serve as a humanistic-based intervention model within school guidance and counseling services.